Characteristics of Sedimentary Microfacies of Late Triassic Yanchang Formation in North-Central Ordos Basin - Jiangwei Wei; Fawang Li; Shikuo Zhang; Hanlie Cheng; Qiang Qin; David Cadasse (Journal of Chemistry)
Sedimentary microfacies refer to the smallest unit with unique rock structure, structure, thickness, rhythm, and other sedimentary characteristics and certain plane configuration rules in the subfacies zone. Sedimentary microfacies research is the most basic sedimentary unit formed in the same or basically the same sedimentary background. Sedimentary microfacies marks are the key to the division of sedimentary microfacies. If we cannot find effective marks, we cannot correctly divide sedimentary microfacies. These marks are mainly obtained from detailed observation of cores. On the premise of fully understanding the regional tectonic background of the study area, the sedimentary facies and sedimentary subfacies types within the oilfield control range are determined. In this study, the single-well facies and profile facies are deeply analyzed by observing and describing the cores of Chang 2 reservoir group in Huangjialing, north-central Ordos Basin, and comprehensively utilizing the data of coring, logging, and core analysis and testing. The basic sedimentary characteristics, types of sedimentary facies and microfacies, and plane distribution of sedimentary facies in this area are systematically studied. The results show that there are mainly three microfacies: underwater distributary channel, natural dike, and distributary bay. Among them, the microfacies of the underwater natural dike are relatively undeveloped, mainly the microfacies of underwater distributary channel and underwater distributary bay. These studies have important practical significance for the later exploration of oil and gas in Ordos Basin.